Evaluasi Kualitas Pemeriksaan Liquor Cerebrospinalis pada Tahap Pra-Analitik, Analitik, dan Pasca-Analitik di Laboratorium Patologi Klinik: Quality Evaluation of Cerebrospinal Fluid Examination at the Pre-Analytical, Analytical, and Post-Analytical Stages in the Clinical Pathology Laboratory - Rinda Aulia Utami; Muhammad Fahmi Aminuddin; Maya Tamara Mawardani; Devi Imelia; La Ode Marsudi (Institut Teknologi Kesehatan dan Sains Wiyata Husada Samarinda, 2025)
Background: Cerebro Spinalis Fluid (CSF) examination can help establish a diagnosis of diseases affecting the central nervous system, including meningitis, increased WBC count, polymorphonuclear ions, and mononuclear ions. Color and clarity examinations are interrelated, and can also detect increased protein in the fluid. Purpose : To determine and observe the techniques and steps of CSF examination. Procedure: Observations were conducted on January 6th – February 6th, 2025 at the Clinical Pathology Laboratory of Abdoel Wahab Sjahranie Regional Hospital, Samarinda. Methods: This type of research is quantitative and uses descriptive analytical methods. Results: This observation obtained 15 samples, the quality of examination at the pre-analytical, analytical, and post-analytical stages was generally good. All samples were accepted and processed according to procedure at the pre-analytical stage. At the analytical stage, protein testing showed 40% positive and 60% negative results with a predominance of mononuclear cells, and no discrepancies were found between parameters. At the post-analytical stage, recording and reporting of results were carried out accurately according to procedure. Conclusion: The CSF examination system in the laboratory has met the basic principles of quality control, but still requires regular evaluation and monitoring to maintain and improve service quality.